The Relationship Between Self-Control and the Tendency to Relapse Among Drug Abusers Undergoing Social Rehabilitation at Sentra Insyaf Medan - Mahnum Lailan; Rina Damayanti Aritonang (Caring: Indonesian Journal of Nursing Science, 2025)
Drug abuse has emerged as a major and deeply concerning challenge, particularly due to the high incidence of relapse among abusers. One of the crucial factors to consider in preventing relapse is self-control. This study aims to identify the relationship between self-control and the tendency for relapse among drug abusers undergoing social rehabilitation at Sentra Insyaf Medan. This research employed a quantitative analytic method with a correlational design, involving 98 respondents selected through purposive sampling based on specific inclusion criteria. Data were collected using two questionnaires: a self-control questionnaire and a relapse tendency questionnaire developed based on indicators of addictive behavior, relapse history, and intention to reuse drugs. Data analysis was conducted using the Spearman Rank correlation test. The results showed that 39.8% of drug abusers had low self-control and 41.8% exhibited a high tendency for relapse. A significant negative relationship was found between self-control and the tendency for relapse, with a p-value of 0.001 (< 0.005) and a correlation coefficient (r) of -0.564, indicating that higher self-control is associated with a lower tendency for relapse. These findings highlight the importance of strengthening rehabilitation programs to support the development of self-control, emotional regulation, and decision-making skills in order to prevent relapse among drug abusers.          Keyword: Self-Control, Relapse Tendency, Drug Abusers, Rehabilitation